TREATMENT OF RADIOTHERAPY FOR SERVIKS CANCER WITH SEPARATION MORE THAN 20 CENTIMETERS USING COBALT-60 AT UNIT RADIOTHERAPY INSTALLATION RADIOLOGY RSUP DR. KARIADI SEMARANG - Galang Harta Widjaya; Fatimah Fatimah; Sudiyono Sudiyono (Jurnal Imejing Diagnostik (JImeD), 2018)
Background: Cervical cancer is a type of cancer that emerges from the cervix. In the early stages of the tumor, treatment therapy will be performed surgically on organs affected by cancer cells, at an advanced stage will be done adjuvant therapy with curative goals through a combination of chemotherapy, surgery, and radiotherapy. In radiotherapy treatment is done with several techniques such as Brachyterapi, IMRT, 3DCRT, and 2D with external aircraft radiation modality with Linac (Linear Accelator) and Cobalt-60. For Brachyterapi (internal radiation) technique, the radiation source is directly placed on the target tumor by using the after loading technique generally, whereas the external radiation techniques of 3DCRT and IMRT are generally performed on external radiation plane using MLC (Multi leaf Collimator) by following the target shape tumors resulting from CT Simulator and TPS (Treatment Planning System) calculations. For IMRT alone the technique used is almost the same as 3DCRT technique. In cobalt-60 is generally used for the treatment of radiation therapy has an average energy of 1.25 MV. At 1.25 MV cobalt energy with 10x10 cm field area will get maximal energy at depth (d max) 0.5 cm and energy will decrease to half (d half) at a depth of 11 centimeter on water media. So that in planning of radiation using cobalt-60 plane have limited separation diameter less than 20centimeter.Methods: This type of research is qualitative with case study approach. the data was collected in October-December 2017 at radiotherapy Installation of Dr. Kariadi General Hospital Semarang by observation methodology, interview with Radiation Oncologist Specialist, Medical Physiciast and Radiographer. the data obtained from the study were analyzed by an interactive model, creating the interview transcripts subsequently reduced and processed within the type of open coding, given within the type of quotations then are often drawn conclusions.Result: The results of this study demonstrate that the management of cervix cancer radiation utilizing 2D procedure in radiotherapy installation of Dr. Kariadi General Hospital Semarang includes patient examination, planning medical physics, verification and radiation treatments. 2D techniques are used pupose to paliative radiation, homogenity of dose and the location of the target volume is close to the Organ at Risk. Field radiation evaluation was performed before first and third irradiation, patient evaluation after five times of radiation and  evaluation after 25rd radiation.Conclusion: The reason for doing the external radiation exposure of cervical cancer with tumor stage further consideration according to the Anatomical Pathology with pT3aN0M0 stage. So the purpose of palliative external radiation. with cervical cancer using cobalt-60 teletherapy air as much as 50 Gy with a fractionation s25 times, and each fractionation with doses of 2Gy. The reason for doing the external radiation exposure of cervical cancer with tumor stage further consideration according to the Anatomical Pathology with pT3aN0M0 stage. So the purpose of palliative external radiation. with cervical cancer using cobalt-60 teletherapy air as much as 50 Gy with a fractionation 25 times, and each fractionation with doses of 2Gy. The reason for doing the external radiation exposure of cervical cancer with tumor stage further consideration according to the Anatomical Pathology with pT3aN0M0 stage. So the purpose of palliative external radiation